Heat stress and stallion fertility - Muhammad Shakeel; Minjung Yoon (Journal of Animal Science and Technology, 2023)
The threat posed by increased surface temperatures worldwide has attracted the attention of researchers to the reaction of animals to heat stress. Spermatogenesis in animals such as stallions is a temperature-dependent process, ideally occurring at temperatures slightly below the core body temperature. Thus, proper thermoregulation is essential, especially because stallion spermatogenesis and the resulting spermatozoa are negatively affected by increased testicular temperature. Consequently, the failure of thermoregulation resulting in heat stress may diminish sperm quality and increase the likelihood of stallion infertility. In this review, we emphasize upon the impact of heat stress on spermatogenesis and the somatic and germ cells and describe the subsequent testicular alterations. In addition, we explore the functions and molecular responses of heat shock proteins, including HSP60, HSP70, HSP90, and HSP105, in heat-induced stress conditions. Finally, we discuss the use of various therapies to alleviate heat stress–induced reproductive harm by modulating distinct signaling pathways.